2005
DOI: 10.1111/j.1528-1167.2005.41604.x
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Sclerosis in Severe Myoclonic Epilepsy in Infancy: A Retrospective MRI Study

Abstract: Summary:Purpose: Severe myoclonic epilepsy in infancy (SMEI; Dravet's syndrome) is a malignant epilepsy syndrome characterized by early prolonged febrile convulsions (PFCs) with secondary psychomotor delay and a variety of therapy-resistant seizures. Although the initial symptoms are repeated PFCs, the MRI performed at the onset of disease shows no hippocampal structural abnormalities. We aimed to assess clinical and serial MRI data of patients with SMEI with a special attention to the temporomedial structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 30 publications
0
41
2
4
Order By: Relevance
“…The SCN1A + surgical case had unilateral hippocampal sclerosis. Previous studies have shown that in a small proportion of patients with Dravet syndrome, hippocampal sclerosis is observed (Striano et al ., 2007 a ), and this may not be present in the early childhood scans (Siegler et al ., 2005). Prospective MRI studies in Dravet syndrome are required.…”
Section: Discussionmentioning
confidence: 99%
“…The SCN1A + surgical case had unilateral hippocampal sclerosis. Previous studies have shown that in a small proportion of patients with Dravet syndrome, hippocampal sclerosis is observed (Striano et al ., 2007 a ), and this may not be present in the early childhood scans (Siegler et al ., 2005). Prospective MRI studies in Dravet syndrome are required.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroradiological studies are normal in most patients (Guerrini and Dravet, 1997) but structural abnormalities such as cerebral or cerebellar atrophy of various degree and focal arachnoid cysts have been anecdotically reported (Dalla Bernardina et al, 1982; Reiner and Renkawek, 1990; Guerrini and Dravet, 1997; Ohki et al, 1997; Dravet et al, 2005). However, only one study systematically investigated structural abnormalities on MRI and found evidence of hippocampal sclerosis (HS) in 10 out of the 14 children with a clinical diagnosis of SMEI (Siegler et al, 2005). Among these, six who had been reported to have normal initial MRI developed HS during the course of the disorder (Siegler et al, 2005).…”
mentioning
confidence: 99%
“…11,19,20 Unilateral or bilateral hippocampal sclerosis is an increasingly recognized finding in patients with Dravet syndrome and/or SCN1A mutations and may develop after an initially normal MRI. 5,19,22 abbreviations EEG = electroencephalography; GEFS+ = generalized epilepsy with febrile seizures plus; ILAE = International League Against Epilepsy; MCD = malformation of cortical development; MTS = mesial temporal sclerosis; SMEI = severe myoclonic epilepsy of infancy. However, other authors have hypothesized that SCN1A mutations may actually protect from hippocampal sclerosis.…”
mentioning
confidence: 99%